Molecular dissection of the glutamine synthetase-GlnR nitrogen regulatory circuitry in Gram-positive bacteria - Brady A. Travis; Jared V. Peck; Raul Salinas; Brandon Dopkins; Nicholas Lent; Viet D. Nguyen; Mario J. Borgnia; Richard G. Brennan; Maria A. Schumacher (Nature Communications, 2022)
How bacteria sense and respond to nitrogen is a key question in microbial physiology. This work unveils the mechanism by which the central nitrogen metabolic enzyme, glutamine synthetase, directly signals nitrogen availability to the GlnR regulator.